The global political economy of trade protectionism and liberalization: trade reform and economic adjustment in textiles and clothing - Heron, Tony (Routledge/RIPE studies in global political economy, 2012)
1. Introduction -- 2. The Multi Fibre Arrangement -- 3. The political economy of trade liberalization in textiles and clothing -- 4. The "winners" and "losers" of trade liberalization in textiles and clothing -- 5. The EU, China and textiles diplomacy under the WTO -- 6. The WTO Agreement on Textiles and Clothing and the Caribbean "offshore" development model -- 7. The African Growth and Opportunity Act and the politics of preference erosion in the WTO Doha "Development" Round -- 8. Conclusions.